The Promotion of Cultural Tourism in Lower Subansiri District of Arunachal Pradesh: An Evolution of Accommodation Facilities and Tourists Arrivals (International Journal of Scientific Research and Management (IJSRM), 2017)
The Lower Subansiri district is one of the oldest district of Arunachal Pradesh with an area of about 3460 sq.km and about 83,030 population (2011) spreading in 536 villages. Geographically, it is an undulating terrain, altitude varies from place to place. The greater part of it falls within the higher mountain zone consisting of tangled peaks and enthralling valleys. The district is lying approximately between 26°55’ to 28°21’ N of latitudes, and 92° 40’ to 94° 21’ E of longitudes. The name of the district derived from the Subansiri River, a tributary of mighty Brahmaputra. The district is rich in natural as well as cultural aspects. Nature has nurtured and groomed the district in the form of superb scenery of majestic mountainous landscape, inter-montane plateau and wonderful sights of colourful tribal cultures which attracts the tourists from within and outside the country. Thus, there lie possibilities for promoting cultural tourism. Cultural tourism is one dimension of such development which can provide benefit to local people both financially and socially. But certain regulatory constraints, lack of basic infrastructure as well as trained manpower hindering the development of the tourism in the distict. Through this paper an attempt has been made to examine the trend of tourist flow and changes in accommodation facilities as a result of promoting cultural tourism based on field investigation and documentation.